A study of the clearance capacity of the dialyser and the incidence of infection when reused. - Adhikari, Khem Kumar (2001)
ABSTRACT: End stage renal disease has become a common disease worldwide. Renal transplantation is beyond the reach of majority of the patients. The common modality of treatment is maintenance hemodialysis for survival and that is also costly and not affordable by most patients especially in the developing countries. To curtail down the cost of maintenance hemodialsis various modifications are being tried and one of the methods of doing so is to reuse the dialyses for multiple times after proper washing, cleaning and reprocessing. Thirty patients n maintenance hemodialysis, twenty males and ten females ranging from eighteen years to seventy-eight years were included in this study to find out the clearance capacity of the dialyser when used for first time and after each reuse for five times and the incidence of infection Hemophan dialyser was used in all the patient and reused after proper processing for five sycessive times. Creatinine clearance of the dialyser was calculated for each use and standard statistical analysis done. At the same time saline effluent cultures were done each time the dialyser was used. No significant declilne in the creatinine clearance of the dialyser was observed for up to three uses. A small but statistically significant decrease in the clearance was observed when the dialyser was used for the fourth time as comared to the first. However when the second use was compared to the fourth and the third use compared to fourth it was found to be insignificant. The clearance in the fourth use could have been affected by temporary cessation of the dialysis due to the intradalytic complications. Therefore in our setup it can be concluded that the dialysers can be used upto four times if proper precautions are taken to avoid the intradialytic complications and the temporary cessation of the dialysis. Similarly on increase in the incidence of infection was observed upto six users. Therefore, reuse of dialyser up to three times is found to be safe and efficient without and decline in the clearance capacity and without any increase in the incidence of infection. However the number of times that the dialyser can be reused is found to be lower than that of the previously published studies. The difference in the number of uses in this study and the reprocessing methods used. Manual reprocessing method was used in this study. Most of the previously published studies have been carried out with the automated reprocessing method and the automated reprocessing is found to generate a higher level of performance leading to an increased in the number of times that the dialyser cab be reused (Gagnon, RF and Kaye M. 1985).